EDUCATION IN A PANDEMIC: OPPORTUNITIES AND THREATS OF DISTANCE LEARNING - Sychenko, Viktor; Вerezynskyi Volodymyr; Vilkhova, Tetiana; Kravchenko, Liubov (Public Administration and Regional Development, 2022)
The article explores the trends in the impact of the COVID-19 pandemic on the education system. Similarities and differences are revealed in the choice of teaching tools and methods by the heads of educational institutions that ensure the work of educational institutions in different countries. It shows how digital technologies and distance learning help students to continue learning even in the face of severe social upheaval. At the same time, the ambiguity of distance education as a vector for the development of education is emphasized: new technologies not only do not contribute to solving the outdated problems of the industry, but also provoke the emergence of new challenges in this area. The authors show that almost all of the technologies listed in the article are currently used to transfer full-time education to an online environment or to distance learning formats. Thus, they can be divided into two main groups: platform and non-platform solutions. In particular, a conditional division into groups is made. The Moodle platform was assigned to one. In the learning environment, it allows you to remotely receive the necessary educational material at any time; it has become an inseparable part of training in higher education institutions. The authors refer to another group the following technologies that work both independently and in interaction with other functional solutions, such as: the transfer of educational content through media channels; conducting classes using social networks, instant messengers and e-mail; replication of "hard" (paper) copies of educational materials and others. As a result of the study, it was concluded that the little experience of digitalization of the world showed how quickly ties between people of different generations can weaken, the content and methods of organizing habitual activities that form social institutions can change. It is noted that the development of any society is largely carried out by improving its social institutions. The changes brought by the pandemic to the life of both the international community as a whole and each individual individually necessitate changes in key public institutions. It has been proved that in the field of education in the near future it will be necessary to revise not only the forms and principles of organization, but also the very foundations of this system.